Theoretical Basis of Character Education as a Foundation for Character Formation - Wildan Mahmudin; R Marfu Muhyidin Ilyas; Aan Hasanah; Bambang Samsul Arifin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Understanding several theories related to character education is expected to be a foundation in understanding and applying character education to every aspect of daily life. This study uses a library research type. With a descriptive qualitative approach. The results of this study are: Moral development includes the development of thoughts, feelings, and behavior according to rules or habits regarding things that a person should do when interacting with others. The essence of cognitive development is the development of formal operational thinking skills characterized by abstract thinking skills and deductive-hypothetical thinking skills. Social development is the acquisition of behavioral skills that are in accordance with social demands. Becoming a person who is able to socialize requires three processes. Among them are learning to behave in a socially acceptable manner, playing an acceptable social role, and developing social traits.